Versengeni és együttműködni? Egy reprezentatív felmérés tanulságai - Sára Khayouti; János Kiss Hubert; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– In this study, we use two representative surveysto investigate how competition and cooperation relate on the individual level and whether (and how) they associate with educational attainment. Our first result is that the correlation between competition and cooperation is positive and significant, even if we take into account the respondent's age, gender, settlement type and region of residency. We also find that competition and cooperation relate in a nonlinear way to educational attainment. Higher levels of competition and cooperation associate with more years in school, but at a decreasing rate. Moreover, too high levels of competition and cooperation correlate with lower levels of educational attainment.
Keywords: D01; D64; D91; 330; competition; cooperation; educational attainment; representative survey